Close‐up: HIV/SIV intasome structures shed new light on integrase inhibitor binding and viral escape mechanisms. (22nd June 2020) - Engelman, Alan N.; Cherepanov, Peter
Abstract : Integrase strand transfer inhibitors (INSTIs) are important components of drug formulations that are used to treat people living with HIV, and second‐generation INSTIs dolutegravir and bictegravir impart high barriers to the development of drug resistance. Reported 10 years ago, X‐ray crystal structures of prototype foamy virus (PFV) intasome complexes explained how INSTIs bind integrase to inhibit strand transfer activity and provided initial glimpses into mechanisms of drug resistance. However, comparatively low sequence identity between PFV and HIV‐1 integrases limited the depth of information that could be gleaned from the surrogate model system. Recent high‐resolution structures of HIV‐1 intasomes as well as intasomes from a closely related strain of simian immunodeficiency virus (SIV), which were determined using single‐particle cryogenic electron microscopy, have overcome this limitation. The new structures reveal the binding modes of several advanced INSTI compounds to the HIV/SIV integrase active site and critically inform the structural basis of drug resistance. These findings will help guide the continued development of this important class of antiretroviral therapeutics. Abstract : Recent single‐particle cryogenic electron microscopy structures of HIV/SIV intasomes (integrase‐DNA complexes) show how clinical integrase strand transfer inhibitors (INSTIs) bind the enzyme active site. The structure of the SIV integrase mutant Q148H/G140S enzyme with INSTI bictegravir (BIC) bound moreover reveals the structural basis of drug resistance. The mutant side‐chains destabilize the coordination shell of the DDE enzyme active site‐magnesium ion cluster that is critical for integrase activity and inhibitor binding.